Ghanaian indigenous conception of real mathematics education in mathematics teaching and learning - Ali, Clement Ayarebilla (Indonesian Journal of Science and Mathematics Education, 2021)
Ghana's rich cultural heritage has not been fully incorporated into mathematics education despite its potential to enhance students' understanding of mathematical concepts. This study explores the integration of Ghanaian cultural elements, including signs, symbols, artifacts, and technology, into mathematics teaching using the Realistic Mathematics Education (RME) approach. A quasi-experimental design with non-equivalent groups was employed, involving 80 students in the experimental group and 70 in the control group. The experimental group was taught using four real mathematics trends, while the control group followed a traditional approach. Data were collected through pretest and posttest assessments, and statistical analysis was conducted using ANOVA and MANCOVA. Findings reveal that Ghanaian indigenous culture is primarily represented through signs, symbols, artifacts, instruments, tools, and technology, with signs and symbols playing the most significant role in supporting students' mathematical understanding. The study concludes that integrating local cultural elements into mathematics teaching enhances students’ problem-solving abilities and deepens their appreciation of cultural heritage. The implications of this study highlight the necessity of incorporating indigenous cultural elements into mathematics instruction to create a more meaningful and contextually relevant learning experience, ultimately fostering both academic success and cultural preservation.